Investigating the Effectiveness of an Educational Escape Game for Increasing Nutrition-Related Knowledge in Young Adolescents: A Pilot Study - Abdollahi, Anna M.; Masento, Natalie A.; Vepsäläinen, Henna; Mijal, Michal; Gromadzka, Monika; Fogelholm, Mikael (Frontiers in Nutrition, 2021)
Objective As a pilot trial under the Games of Food consortium, this study assessed the effectiveness of an educational escape game alongside a self-study method as a nutrition knowledge intervention. Furthermore, this study explored the use of an escape game as an educational tool for young adolescents. Materials and methods Altogether three schools participated, one from Finland and two from the UK. Baseline questionnaires assessing knowledge were administered before intervention day. Participants from each class were randomly allocated by the researchers into either the escape game condition, where participants played a nutrition education escape game with a focus on plant-based protein sources, or the self-study condition, where participants received an educational leaflet with identical content. In addition to the knowledge post-assessment, the educational escape game condition answered an enjoyment and intrinsic motivation questionnaire to evaluate the game experience. Paired t-tests were used to determine significant changes within intervention conditions and ANCOVA was used to estimate the differences in knowledge. Results The participants were 130 children (11-14y), divided into educational escape game (n=68) and self-study (n=62) conditions. Both the educational escape game (20.7 vs. 23, p<0.001) and self-study (21.1 vs. 23.1, p=0.002) had improved overall knowledge scores. No significant differences in gained knowledge existed between groups. Of the educational escape game participants, 60% reported the game as mostly enjoyable and 46% reported added use and value for learning. Conclusion The educational escape game condition was comparable to the self-study method for nutrition education in adolescents. However, since the educational escape game provides an enjoyable experience that may enhance intrinsic motivation to promote learning and possible behavior change, the use of escape games for nutrition education warrant further investigation.